Why should we care about FAIR? - Harrower, Natalie (Septentrio Conference Series, 2020)
See RECORDING. For a long while, Open Access to publications was the key focus of the Open Science agenda, but suddenly, everyone is talking about data and other research outputs. What are these? Why should we pay attention to them? What’s the difference between FAIR data and Open data, and why should scholars care about any of this? These are the kinds of questions that have been floating around as funders like the European Commission start to mandate the sharing of data, software, and other outputs that support publications. And while the drive towards FAIR sharing is meant to be applied across all research domains and disciplines, the discussion often focuses on ‘big data’ or data from the natural sciences, collected in laboratories or processed on high performance super computers. Where does this leave humanities scholars? What kinds of data and other research outputs are created here? What considerations are particular to the humanities? In February 2020, after an open consultation process that received over 200 comments plus a number of multi-page submissions, ALLEA published “Sustainable and FAIR Data Sharing in the Humanities: Recommendations of the ALLEA Working Group E-Humanities", https://doi.org/10.7486/DRI.tq582c863. The report is structured around the research data lifecycle, providing concrete recommendations for sustainable FAIR sharing. This talk will highlight some of the key challenges faced by humanities scholars in this realm, look to where alliances can be built outside of academia, and dive into the dissemination possibilities that are created through the FAIR sharing of humanities research data.